An Overview of Optical Fibre Sensors for Medical Application - Mazuina, Mohamad; Hadi, Manap (Penerbit Universiti Malaysia Pahang, 2014)
Optical techniques developed for sensing purposes proved ti be completely realized in many application fields, ranging from aerospace, industry, process control and medical. The capabilities of these sensors are generally enhanced when a bulk optical fibre technology. There is a growing need for a real time and low cost technology because of the expense and time constraints associated with modern laboratory analysis. This us certainly due the growing interest in aptoelectronics, but also the very satisfactory performance and reliability that optical fibre sensor are now able to provide. This paper focuses on the advantages that optical fibre sensos offer to the biomedical field, recalls the basic working principles of sensing and discusses some example.